Acoustic Losses in Cryogenic Hydrogen at Transitions Between Tubes of Different Diameters - Kian Conroy; Konstantin I. Matveev (Hydrogen, 2025)
Acoustic oscillations in cryogenic systems can either be imposed intentionally, as in pulse-tube cryocoolers, or occur spontaneously due to Taconis-type thermoacoustic instabilities. To predict the propagation of sound waves in ducts with sudden changes in cross-sectional areas, minor losses associated with such transitions in oscillatory flows must be known. However, the current modeling approaches usually rely on correlations for minor loss coefficients obtained in steady flows, which may not accurately represent minor losses in sound waves. In this study, high-fidelity computational fluid dynamics simulations are undertaken for acoustic oscillations at transitions between tubes of different diameters filled with cryogenic hydrogen. The variable parameters include the tube diameter ratios, temperatures (80 K and 30 K), and acoustic impedances corresponding to standing and traveling waves. Computational simulation results are compared with reduced-order acoustic models to develop corrections for minor loss coefficients that describe transition losses in sound waves more precisely. The present findings can improve the accuracy of design calculations for acoustic cryocoolers and predictions of Taconis instabilities.